The Main Dividing Lines Between the European Commission and the Polish in the Field of Energy Policy - Motowidlak, Tomasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
Due to the dominant role of coal in the structure of energy production and the high dependence on gas imports from the Russian Federation and together with politicization of economic relations with this country, Poland is particularly exposed to the unfavorable influence of some European Commission’s policies and initiatives in regards to energy policy. The paper has shown that they mainly concern the gas market and climate protection and include, first of all, the drive to increase the supply of Russian gas to the European Union and to reduce CO2 emissions by energy producers. The reciprocal links between these policies and initiatives and the economic and political interests of Poland have been presented. The conclusions drawn from this paper may include the possible negative effects of these links and proposals how to direct our country’s energy policy in order to limit or avoid these effects.